MAXIMA: an experiment to measure temperature anisotropy in the cosmic microwave background - Lee, A; Ade, P; Balbi, A; Bock, J; Borrill, J; Boscaleri, A; Crill, B; Bernardis, P; Castillo, H; Ferreira, P; Ganga, K; Hanany, S; et al. (1999)
We describe the MAXIMA experiment, a balloon-borne measurement designed to map temperature anisotropy in the Cosmic Microwave Background (CMB) over a wide range of angular scales (multipole range 80 < l < 800). The experiment consists of a 1.3 m diameter off-axis Gregorian telescope and a receiver with a 16 element array of bolometers cooled to 100 mK. The frequency bands are centered at 150, 240, and 410 GHz. The 10' FWHM beam sizes are well matched to the scale of acoustic peaks expected in the angular power spectrum of the CMB. The first flight of the experiment in its full configuration was launched in August 1998. A 122 sq-deg map of the sky was made near the Draco constellation during the 7 hour flight in a region of extremely low galactic dust contamination. This map covers 0.3% of the sky and has 3200 independent beamsize pixels. We describe the MAXIMA instrument and its performance during the recent flight.